Decay Process of Serpentinite: The Case of the San Giovanni Baptistery (Florence, Italy) Pavement - Alba Patrizia Santo; Beatrice Agostini; Carlo Alberto Garzonio; Elena Pecchioni; Teresa Salvatici (Applied Sciences, 2022)
Serpentinite is a low-grade metamorphic rock derived from the transformation of ultramafic rocks. Mainly because of its aesthetic characteristics it has been widely used as a building and ornamental stone. “Verde di Prato” is the most common local name used in Tuscany to refer to this type of rock, historically quarried in this area and used for many centuries in a large number of monuments of this region. In this paper, we report the results of a study carried out on the serpentinite from the pavement of the Florence baptistery, to properly characterize it from a physical point of view, describe the rock conservation state, and understand the phenomena responsible for its decay. The studied rock displays numerous forms of decay including fractures, loss of material, erosion, discolouration and efflorescence. X-ray diffractometer analyses of the efflorescence revealed the presence of numerous salts whose formation can be imputed to multiple, possibly concomitant, causes such as the high relative humidity and the variation of inside temperature, the presence of concrete and/or cementitious mortars in the subsoil, atmospheric pollution and the burial ground existing close the baptistery.